2014
DOI: 10.1002/app.41784
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of transfer of wine aroma compounds through PET bottles

Abstract: Aroma compound could be lost during food storage in polymer packaging by transfers through material. The aim of this study was to develop a method that allows evaluating wine aroma compounds permeation through active PET bottles. A semiquantitative method has been adapted to the system. Results showed a regular permeation of all studied aroma compounds but a high variation between replicates. In active PET bottle containing 1% of oxygen scavenger, amount lost by permeation after 12 months storage at 20 C was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…One of the advantages in the coating approach is that relatively high gas barrier enhancement is possible to various gas components including oxygen, carbon dioxide, water vapor, and flavors. This favors the quality retention of beverages where quite complex combinations of flavors contribute to unique taste and mouth-feeling, for example, seen in wine and beer [15][16][17]. Another advantage lies in high recyclability.…”
Section: Thin Film Coating For the Gas Barrier Enhancement Of Pet Botmentioning
confidence: 99%
“…One of the advantages in the coating approach is that relatively high gas barrier enhancement is possible to various gas components including oxygen, carbon dioxide, water vapor, and flavors. This favors the quality retention of beverages where quite complex combinations of flavors contribute to unique taste and mouth-feeling, for example, seen in wine and beer [15][16][17]. Another advantage lies in high recyclability.…”
Section: Thin Film Coating For the Gas Barrier Enhancement Of Pet Botmentioning
confidence: 99%
“…The evolution of the aromatic profile of rose wine packaged in different materials such as glass, virgin and recycled PET bottles was studied by Dombre et al [10,33]. The appearance of new compounds (furfural derivatives, 5-hydroxymethyl furfural, and ethyl pyruvate or dioxanes) independently of the packaging type was observed.…”
Section: Influence Of Packaging On Beverage Conservation and Drawbackmentioning
confidence: 99%
“…Results of Dombre and Giovanelli showed that PET bottles with oxygen scavenger cause less aroma loss . They explained this behaviour by less oxidation due to activity of an oxygen scavenger . Berlinet showed improved vitamin C and colour preservation in bottles with oxygen scavenger compared with bottles without .…”
Section: Introductionmentioning
confidence: 96%
“…Poly(ethylene terephthalate) (PET) bottles are relevant for packaging of beverages and oils . Many of these fillings are sensitive to oxygen such as beer, fruit juices, wine, milk and oil . Oxygen sensitivity of beverages is reported to be 1–4 mg/kg for beer, 3 mg/kg for wine, 30–40 mg/kg for soy oil and 85 mg/kg for orange juice .…”
Section: Introductionmentioning
confidence: 99%